2008
DOI: 10.1155/2008/609684
|View full text |Cite
|
Sign up to set email alerts
|

The Creatine Transporter Gene Paralogous at 16p11.2 Is Expressed in Human Brain

Abstract: Autism is a complex neurodevelopmental disorder characterized by impairment of social interaction, language, communication, and stereotyped, repetitive behavior. Genetic predisposition to autism has been demonstrated in families and twin studies. About 5–10% of autism cases are associated with chromosomal abnormalities or monogenic disorders. The identification of genes involved in the origin of autism is expected to increase our understanding of the pathogenesis. We report on the clinical, cytogenetic, and mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…Kaya et al [18] An autism-predisposing chromosomal aberration (Xq12-q13.3 duplication) was detected Abu-Amero et al [19] They described autism in partial 9 p duplication syndrome Tunisia Bayou et al [20] They found a boy with autism carrying a de-novo translocation t (7;16) (p22.1; p11.2) responsible for the expression of the creatine transporter paralogous in the testis and brain Bayou et al [21] This study described a Tunisian boy with autism with 7p22.1, which was identified as a positional candidate region for autism on chromosome 7 Morocco Ouldim et al [22] A case report of a boy with infantile autism and cytogenetic abnormalities on chromosomal region 15q11-q13 Qatar…”
Section: Saudi Arabiamentioning
confidence: 99%
“…Kaya et al [18] An autism-predisposing chromosomal aberration (Xq12-q13.3 duplication) was detected Abu-Amero et al [19] They described autism in partial 9 p duplication syndrome Tunisia Bayou et al [20] They found a boy with autism carrying a de-novo translocation t (7;16) (p22.1; p11.2) responsible for the expression of the creatine transporter paralogous in the testis and brain Bayou et al [21] This study described a Tunisian boy with autism with 7p22.1, which was identified as a positional candidate region for autism on chromosome 7 Morocco Ouldim et al [22] A case report of a boy with infantile autism and cytogenetic abnormalities on chromosomal region 15q11-q13 Qatar…”
Section: Saudi Arabiamentioning
confidence: 99%
“…This protein is expressed in most human tissues, predominantly in the brain, heart, and muscle (Von Figura et al 2001;Abplanalp et al 2013), but two pseudogenes, SLC6A10PA and SLC6A10PB (Von Figura et al 2001;Höglund et al 2005;Ndika et al 2014), located on chromosome 16p11.2 have also been found. These pseudogenes are particularly expressed in the testis (Von Figura et al 2001) and brain (Bayou et al 2008). Recently, a second protein (MCT12) identified several years ago (Halestrap and Meredith 2004) has been associated to patients with a particular syndrome (Vandekerckhove et al 2007;KloeckenerGruissem et al 2008) and Cr transport defect (Abplanalp et al 2013).…”
Section: Metabolism Of Creatinementioning
confidence: 99%
“…Curiously, the pseudogenes of the Cr transporter (SLC6A10PA and SLC6A10B) are found in this chromosomal region (Von Figura et al 2001;Höglund et al 2005;Ndika et al 2014). Interestingly, Bayou et al (2008), described a de novo translocation t(7;16)(p22.1;p11.2) in a boy with autism, which breakpoint involves the SLC6A10P. Investigations in patients with ASDs focused on the study of cerebral abnormalities of metabolites using 1 H-MRS have demonstrated alterations of Cr in different brain regions although with some discrepancies.…”
Section: Creatine In Autism Disordersmentioning
confidence: 99%
“…[82] In some of the most severe metabolic diseases, like adenylosuccinase defi ciency or creatine defi ciency syndromes, neurological and behavioral symptoms are probably not caused by defi ciency of metabolites, but are more likely due to the toxic effects of the accumulating substances on the brain. [83][84][85] A direct role in modulation of dopaminergic and serotoninergic neurotransmission systems and axonal guidance has been hypothesized for the adenosine deaminase defi ciency as a pathologic mechanism for the development of autistic symptoms. [86] The role of mitochondrial disorders has been revitalized by the association between autism and variants of the SLC25A12 gene, which encodes the predominant isoform of the mitochondrial aspartate (asp)/glutamate (glu) carrier (AGC) in the brain.…”
Section: Metabolic Diseasesmentioning
confidence: 99%